Variations and characteristics of particulate matter, black carbon and volatile organic compounds in primary school classrooms. (10th April 2020) - Li, Kangwei; Shen, Jiandong; Zhang, Xin; Chen, Linghong; White, Stephen; Yan, Mingming; Han, Lixia; Yang, Wen; Wang, Xinhua; Azzi, Merched
Abstract: The effect of human activities on the characteristics and variations of indoor air pollutants is poorly understood, in particular for the classroom environment due to the limited reports at present. In this study, an observational campaign (17 days) was carried out in two selected classrooms (one equipped with air purifier) in a primary school of Hangzhou, China. Highly time-resolved particulate matter (PM) and black carbon (BC) were measured using Aerodynamic Particle Sizer (APS) and Aethalometer, and the diurnal variations of PM2.5, PM10, PM20 and BC were characterized in detail. It was found that the student activities occurred throughout the daytime and could result in rapid changes in air pollutants. For example, the daytime student activities (e.g., chasing and running) strongly enhanced the PM level and changed PM diurnal pattern, in particular for coarse particles (2.5–10 μm) with short-term spikes at intervals, which was not observed under vacant conditions. The indoor BC did not show clear diurnal patterns, regardless of working days and weekends. Through absorption exponent analysis, it was inferred that the source of indoor BC was stable at most of the time, and possibly related to traffic emission. Besides, three volatile organic compounds (VOCs) samples were collected from the two classrooms, and the laboratory analysis results showed that oxygenated VOCs was a major contributor to indoor VOCs. Through inter-comparison analysis of indoor and outdoor samples, it was further found that the VOC profile of classrooms has a similar pattern with outdoor environments. Finally, the most abundant VOC species of classroom environment were identified, and their potential sources were estimated. Highlights: Variations and characteristics of PM, BC and VOCs were characterized in classroom environment. Student activities were identified as a major source of classroom PM under occupied conditions. The source of indoor BC was stable at most of the time. The VOC profile of classroom environment showed similar pattern with outdoor air.